Analisis Yuridis Normatif Undang-Undang Perlindungan Tindak Pidana Kekerasan Terhadap Anak - Muhammad Farhan Hasan; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Domestic Violence or abbreviated as KDRT is a problem that is often found throughout the world and this is a topic that has never been resolved. Domestic violence is a social phenomenon that has been going on for a long time in some households in the world. This problem is a serious problem that involves violations of Human Rights (HAM). Child violence includes physical, psychological, sexual violence, and neglect. UNICEF defines violence against children as "All forms of physical and emotional abuse, sexual abuse, neglect, or commercial or other exploitation that result in actual or potential harm to the development, health, and survival of the child or to his or her dignity in the context of a relationship of responsibility, trust, or power". There are many theories related to violence against children, including theories related to stress in the family. Stress in the family can come from children, parents, or situational. Stress comes from children, for example children with different physical, mental, or behavioral conditions, toddlers, and children with chronic diseases. Stress comes from parents, for example parents with mental disorders, parents who have been victims of violence in the past, parents who have too high expectations of their children, and parents with high discipline